(untitled) (Archives of Criminology, 1996)
Among the negative side-effects of the fall of "Realsozialismus" in Central and Eastern Europe and the process of political, social and economic transformations initiated in 1989 there was a deterioration of internal safety in those countries. According to a popular opinion, this was manifested, among other things, by a growth - a rapid one in many instances - in the extent and intensity of crime, and also in negative changes of its structure which consisted in a particularly fast growth of tle most serious crime or emergence of its new and very dangerous forms, hitherto unknown in those countries. From this viewpoint, criminological literature in all those countries without exception has recently been presenting an extremely pessimistic picture of a growing threat of crime which can at any moment get out of control. As a consequence, fear of crime is growing in societies involved, and appeals can be heard more and more often from politicians that “law and order” be instituted. The present paper does not aim at negating either the growth of crime in post-Communist societies itself or the negative changes of the structure of crime. It is our aim first of all to compare the state of crime that follows from the two basic modern sources of information on this area, that is oflicial statistics of crime and victimization surveys, and to point to some related problems. The analysis is limited to two countries, Germany and Poland. Concerned in the former case is, of course, mainly analysis of phenomena found in the new federal lands of united Germany, that is the territory of former GDR, but also consequences of the union for the state of crime in Germany as a whole. One of the basic problems posed by analysis of extent, intensity and dynamics of reported crime, that is crime recorded in oflicial statistics in countries of Central and Eastern Europe, is reliability of statistical data from the period of “Realsozialismus” which serve as the point of departure of all comparisons. The growth in reported crime in the territory of former GDR has indeed been dramatic after 1990; yet the point of departure for comparisons involved here are GDR police statistics which showed the extent of reported crime as 10% of that in “old” FRG. Today, German criminologists agree that GDR crime statistics were regularly “improved” for ideological and political reasons, the real extent of crime being much higher there. Similar problems can be found in Poland where a rapid growth in reported crime took place only once in principle, that is in 1990. Later on, the extent of reported crime became stabilized at the new level “established” in 1990. It is highly improbable that the impact of social and economic reform on crime in Poland was limited to a “big bang” in 1990 and then ceased. Also here, we dealt rather with a specific statistical artifact and not with a single rapid growth in the extent of crime. What also speaks for this thesis is the fact that crime used to be “under-recorded” in police statistics in Poland as well through a policy of extremely selective reception by the police of information about offenses. Abandonment of this practice after 1989 resulted in a serious growth of recorded crime. Appraising the dynamics of reported crime in Central and Eastern Europe, one should also bear it in mind that the growth in crime there not necessarily followed the breakdown of “Realsozialismus”. In many countries, former USSR in particular, the growth in crime actually preceded change. Also in recent years, Central and East-European statistics have by no means been showing a constant and rapid growth in reported crime. There were rather fluctuations (if quite rapid at times), followed by a recent downward trend in some of the countries involved. Still another important problem is comparison of the extent of reported crime in post-Communist and in developed Western societies. Discussing the “flood” of crime in Central and Eastern Europe, one tends to forget that in most cases, the actual extent of crime in the region is still much lower than in most countries of Western Europe. Comparison of the situation in Germany and Poland may serve as an example here. I ulated. As far as possible, the state of crime in post-Communist societies should also be appraised on the basis of sources other than the official statistics. Helpful here can be first of all data from victimization surveys, alas still a rarity in Central and Eastern Europe. Yet basing on available data for Germany and Poland (chiefly from the International Crime Survey of 1992) it can be stated that victimization surveys show an extent of real crime much higher than the one that follows from official statistical data. This means a very high dark number of crime in Poland and elsewhere in the region, caused probably by the people’s very low tendency to report facts of victimization to the police. At any rate, from data on victimization it follows that the extent of real crime in Poland is higher as compared to Germany. This is not to say, though, that crime in Poland “breaks all the records”. With some exceptions concerning chiefly offenses against property such as theft and pickpocketing, Poland has an average extent of crime judging by European “standards’” in this respect. Basing on data from victimization surveys, also the territorial differentiation of the extent of crime in Germany and Poland can be analyzed. The basic problem in Germany is the noticeable difference between southern and northern lands, the latter having a much higher extent of crime, and also the process of the new lands “catching up” with or even “outstripping” the old ones in this respect during the last five years. Quite distinct regularities can also be found in Poland; some of them are known from earlier literature. Thus first of all, there is a noticeably higher extent of crime in Western and Northern Territories of Poland and a low extent in Wielkopolska region. It is interesting to correlate those regularities with selected demographic and socio-economic data on individual regions of the two countries. In Germany, unfavorable values of those indices found in the north of “old” FRG and in former GDR are rather explicitly correlated with a higher extent of crime. In Poland where territorial differentiation of the indices is less distinct, some regularities in this respect can nevertheless be found, too. At the samo time it seems, though, that the extent of crime in Poland is the highest in regions where, due to specific local features, the social costs of reform are the greatest and most painful.